2022
DOI: 10.1021/acs.orglett.2c00294
|View full text |Cite
|
Sign up to set email alerts
|

Ligand- and Counterion-Assisted Phenol O-Arylation with TMP-Iodonium(III) Acetates

Abstract: High reactivity of trimethoxyphenyl (TMP)iodonium(III) acetate for phenol O-arylation was achieved. It was first determined that the TMP ligand and acetate anion cooperatively enhance the electrophilic reactivity toward phenol oxygen atoms. The proposed method provides access to various diaryl ethers in significantly higher yields than the previously reported techniques. Various functional groups, including aliphatic alcohol, boronic ester, and sterically hindered groups, were tolerated during O-arylation, ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…The TMP unit of the iodonium acetate reagent ( 2 ) served as a dummy ligand to transfer the aryl group and increased the reactivity and selectivity of the O ‐arylation process.Thus, the reaction of 1 a with diphenyliodonium acetate generated 3 aa and 4 aa in 44% and 24% yields, respectively, representing decreases in both reactivity and selectivity compared to when TMP‐iodonium acetate was used as the arylating agent (Scheme 6 and Table S7). One possible explanation for the effect of TMP is that the ortho ‐methoxy groups of TMP coordinated with the iodine center to enhance the anionic character of the amidate oxygen atom, [25a,b] promoting ligand coupling to achieve O ‐arylation. Furthermore, the arylation proceeded at the oxygen atom rather than at the tert ‐butoxy‐bearing nitrogen atom owing to a steric clash with the methoxy groups of the TMP ligand (Scheme S1).…”
Section: Methodsmentioning
confidence: 99%
“…The TMP unit of the iodonium acetate reagent ( 2 ) served as a dummy ligand to transfer the aryl group and increased the reactivity and selectivity of the O ‐arylation process.Thus, the reaction of 1 a with diphenyliodonium acetate generated 3 aa and 4 aa in 44% and 24% yields, respectively, representing decreases in both reactivity and selectivity compared to when TMP‐iodonium acetate was used as the arylating agent (Scheme 6 and Table S7). One possible explanation for the effect of TMP is that the ortho ‐methoxy groups of TMP coordinated with the iodine center to enhance the anionic character of the amidate oxygen atom, [25a,b] promoting ligand coupling to achieve O ‐arylation. Furthermore, the arylation proceeded at the oxygen atom rather than at the tert ‐butoxy‐bearing nitrogen atom owing to a steric clash with the methoxy groups of the TMP ligand (Scheme S1).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, our group developed the O -arylation of phenol derivatives using TMP-iodonium(III) acetate, which exhibits extremely high reactivity induced by the cooperative double-assistance of TMP ligands and acetate anions. 21 ­Methoxy groups at the ortho -positions of TMP ring coordinates with the iodine(III) center to enhance the basicity of acetate anion, which promotes the deprotonation of phenols. In this study, we focused on the N -arylation of N -methoxysulfonamides and N , O -protected hydroxylamines, which is an efficient method to produce synthetic key intermediates for biologically active compounds.…”
Section: Table 1 Optimization Of Reaction Conditions Fo...mentioning
confidence: 99%
“…Diaryliodonium salts were synthesized according to our previous reports. 19e 21 N -Methoxysulfonamides and N , O -protected hydroxylamines were prepared according to the reported methods in literature (see Supporting Information). 8g 29 All reactions that required heating were performed using an oil bath as the heating source.…”
mentioning
confidence: 99%
“…Additionally, Muñiz et al found that the acetate counterion was more effective than chloride, hexafluorophosphate, and trifluoromethane sulfonate for the borylation of diaryliodonium(III) salts [ 12 ]. Recently, our group has developed a new method for phenol O -arylation using aryl(2,4,6-trimethoxyphenyl)iodonium(III) acetates [ 13 ]. In this process, the acetate ligand acted as a base to activate the phenol group and positioned it in proximity to accomplish the smooth S N Ar reaction.…”
Section: Introductionmentioning
confidence: 99%